Wolf Lepenies: Homo Europaeus Intellectualis Revisited - Kwiek, Marek (My University, 2003)
Questions about the intellectual's place and role in society, his tasks and obligations, the status he ascribes to himself and that society ascribes to him have recently become a significant part of the ongoing discourse in the humanities. There are different reasons in different countries for this, but whether in English-speaking countries, in Germany or, especially, in France, questions about the intellectual have been important points of reference in numerous discussions at the end of the 20th century. Lepenies' thinking convincingly shows that the dominating French discourse on the subject requires a significant supplement today, for it depicts merely a part of a larger whole which does not confine itself to France aloneFrench questions about the intellectual (from the Dreyfus affair at the turn of the 20th century to Sartre to, in turn, le silence des intellectuels in the eighties of the last century) do not exhaust the catalogue of all the questions that can and should be asked today; nor do they restrict our account of the issue of the intellectual to the adventure of being seduced by the Marxist (or Stalinist) thinking which started with the October Revolution of 1917 progressing to the middle of the seventies on the part of French writers and philosophers, followed only by their disappointment with and gradual distancing from it after the Algerian war of independence and the events of 1956 (for it is, indeed, possible to see the history of French intellectuals of the 20th century also from such a perspective); furthermore, these questions, heading mainly back through history - and mainly to that of the 20th century France - basically pass in silence the present and the future.
Keywords: Wolf Lepenies; intellectuals; Central Europe; postcommunist countries; transition economies; Melancholie und Gesellschaft; Die Drei Kulturen; Aufstieg und Fall der Intellektuellen in Europa; German intellectuals; French intellectuals; French philosophy; melancholy and society; between literature and science; philosophy and literature; engagement; political involvment; philosophy and politics; Eastern Europe; postcommunist transition; role of the intellectual; public role; academic profession